2005
DOI: 10.1103/physrevlett.94.111601
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity in Strongly Interacting Quantum Field Theories from Black Hole Physics

Abstract: The ratio of shear viscosity to volume density of entropy can be used to characterize how close a given fluid is to being perfect. Using string theory methods, we show that this ratio is equal to a universal value of variant Planck's over 2pi/4pik(B) for a large class of strongly interacting quantum field theories whose dual description involves black holes in anti-de Sitter space. We provide evidence that this value may serve as a lower bound for a wide class of systems, thus suggesting that black hole horizo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

238
3,382
3
13

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,862 publications
(3,687 citation statements)
references
References 25 publications
238
3,382
3
13
Order By: Relevance
“…Starting from the definition of π x in (2.8), it is then easy to infer that 10) where, in accord with the previous discussion, the overall sign has been chosen in such a way that π x < 0 implies X ′ > 0, meaning that the string trails behind its boundary endpoint.…”
Section: String In a Rotating D3-brane Backgroundmentioning
confidence: 80%
“…Starting from the definition of π x in (2.8), it is then easy to infer that 10) where, in accord with the previous discussion, the overall sign has been chosen in such a way that π x < 0 implies X ′ > 0, meaning that the string trails behind its boundary endpoint.…”
Section: String In a Rotating D3-brane Backgroundmentioning
confidence: 80%
“…Nonetheless, in particular the shear viscosity cannot be arbitrarily small due to unitarity [5]. Besides, in weak coupling certain relations hold among different transport coefficients, cf.…”
Section: Introductionmentioning
confidence: 99%
“…One of the surprising results in Au+Au collisions at the RHIC is the strong azimuthal anisotropy observed in mid-central collisions. The comparison of the experimental data on v 2 with the hydrodynamic model calculations has revealed that the produced matter behaves like a "perfect" fluid with the viscosity close to the conjectured low limit by AdS/CFT [5]. As a result, the measurement of v 2 in differential form will be primarily important to learn the collective properties, such as the viscosity, of the fluid-like matter and the equation-of-state.…”
Section: Elliptic Flowmentioning
confidence: 99%